Kedudukan Jaksa sebagai Pengacara Negara dalam Lingkup Perdata dan Tata Usaha Negara - Muhammad Yusuf; Slamet Sampurno; Muhammad Hasrul; Muhammad Ilham Arisaputra (Fakultas Hukum Universitas Surabaya, 2019)
The term Prosecutor as a state lawyer is not clearly stated in the Prosecutor's Law. Implementation of the functions of the Prosecutor as state attorney in the civil and administrative sphere of the state follows the flow and procedures for settlement of civil disputes and state administration in general. To optimize the implementation of the Prosecutor's function as a state lawyer, the Prosecutor must be provided with education and training regarding civil law and constitutional law/state administrative law. Therefore, the institutionalization of the State Attorney Attorney is also needed so that if a lawsuit involving the interests of the state occurs, there will be no difficulty in appointing and determining the Prosecutor acting as the State Attorney.